Echo and ringing of optical pulse in finite photonic crystal with superconductor and dispersive dielectric - Ooi, Chong Heng Raymond; Kam, C.H. (Optical Society of America, 2010)
We study the transient pulse propagation in one-dimensional photonic crystal. Two new effects are identified: double reflection and slow-light ringing of transmitted and reflected pulses. We analyze these effects in superconductor-dielectric photonic crystal around the polariton resonance region of the dielectric material. Distinct double-polariton dispersions and narrow peaks in the transmission and reflection spectra are found when the plasma gap and the polariton gap of the dielectric overlap. Potential applications of these effect are discussed. (C) 2010 Optical Society of America